Hydrogel fiber films, methods of making and using the same

CN122960022APending Publication Date: 2026-10-23TSINGHUA UNIVERSITY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610929872.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是双网络水凝胶同样存在恢复能力差、制造困难、难以形成多孔薄膜结构等技术难题

Benefits of technology

本发明提出的水凝胶纤维薄膜具有良好的机械性能和拉伸性能,同时还具有良好的粘附能力,能够作为优良的超薄粘附传质层,在电生理监测领域中具有广泛的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application provides a hydrogel fiber film, a preparation method and application thereof, and specifically relates to a hydrogel fiber film, which comprises a fiber film base layer and a double-network hydrogel, the double-network hydrogel comprises sodium alginate-acrylamide or polyvinyl alcohol-glycerol / gelatin, and the fiber film base layer comprises an electrospun fiber film; wherein the fiber film base layer has a porous structure, and the double-network hydrogel is arranged in the porous structure of the fiber film base layer. The hydrogel fiber film has good mechanical properties and tensile properties, and also has good adhesion, can be used as an excellent ultrathin adhesive mass transfer layer, and has a wide application prospect in the field of electrophysiological monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wearable sensor technology. Specifically, it relates to hydrogel fiber films, their preparation methods and applications, and more specifically, it relates to hydrogel fiber films, their preparation methods, the use of hydrogel fiber films in the preparation of wearable sensors, and the performance of wearable sensors. Background Technology

[0002] Hydrogels are polymeric materials that can rapidly absorb and retain large amounts of water molecules while remaining insoluble in water. Their hydrogel matrix forms a three-dimensional polymer network structure. Due to their wetting and flexibility, hydrogels are widely used in flexible sensors, flexible actuators, and human-machine interfaces. In recent years, significant progress has been made in designing and manufacturing hydrogel-based flexible sensors. However, the relatively low mechanical properties of traditional hydrogels, and the inherent relationship between hydrogel thickness and mechanical properties, limit their application in flexible sensors.

[0003] To improve the mechanical properties of synthetic hydrogels, previous researchers have introduced dual-crosslinked networks, resulting in hydrogels with better toughness or tensile strength. First, a highly crosslinked three-dimensional network is formed, followed by the introduction of a second-level network onto the first-level network framework. Through this dual-network approach, the hydrogel can exhibit significant deformation while maintaining water saturation. However, dual-network hydrogels also face technical challenges such as poor recovery ability, manufacturing difficulties, and the inability to form porous thin film structures.

[0004] Therefore, it is still necessary to further develop a hydrogel film that can tightly bind to human skin and other biological tissues and has good breathability and mechanical properties in order to improve the stability, low noise and other properties of physiological signal sensors. Summary of the Invention

[0005] This application is based on the inventor's discoveries and understanding of the following facts and problems: In wearable flexible sensors related to hydrogels, the quality of bioelectrical signal acquisition is often determined by the good integration of the hydrogel with biological tissues such as human skin. This invention introduces electrospun fiber films into a dual-network hydrogel, unexpectedly discovering that this significantly improves the performance of the hydrogel fiber films while also enhancing their adhesion.

[0006] Therefore, in a first aspect, the present invention provides a hydrogel fiber film. According to an embodiment of the present invention, the hydrogel fiber film comprises: a fiber film base layer and a dual-network hydrogel, wherein the dual-network hydrogel comprises sodium alginate-acrylamide or polyvinyl alcohol-glycerol / gelatin, and the fiber film base layer comprises an electrospun fiber film; wherein the fiber film base layer has a porous structure, and the dual-network hydrogel is disposed within the porous structure of the fiber film base layer. The hydrogel fiber film proposed in this invention possesses good mechanical and tensile properties, as well as good adhesion ability, and can serve as an excellent ultrathin adhesive mass transfer layer, showing broad application prospects in the field of electrophysiological monitoring.

[0007] In a second aspect, the present invention provides a method for preparing the aforementioned hydrogel fiber film. According to an embodiment of the present invention, the method includes: placing a fiber film substrate in a dual-network hydrogel precursor solution and performing a gelation treatment to obtain the hydrogel fiber film. The hydrogel fiber film prepared by the method proposed according to the present invention possesses good mechanical and tensile properties, as well as good adhesion ability, and can serve as an excellent ultrathin adhesive mass transfer layer, showing broad application prospects in the field of electrophysiological monitoring.

[0008] In a third aspect, the present invention proposes the use of the aforementioned hydrogel fiber film in the fabrication of wearable sensors. The wearable sensor proposed by the present invention possesses excellent mechanical properties, adhesion, and biocompatibility, enabling it to achieve good adhesion to skin and other films.

[0009] In a fourth aspect, the present invention provides a wearable sensor. According to an embodiment of the present invention, the wearable sensor comprises the hydrogel fiber film described above. The wearable sensor proposed in this invention possesses good mechanical properties, adhesion ability, biocompatibility, etc., and can achieve good adhesion to skin and other films.

[0010] The beneficial effects of this invention are at least as follows: The hydrogel fiber film proposed in this invention has good mechanical and tensile properties, as well as good adhesion ability, and can serve as an excellent ultrathin adhesive mass transfer layer, with broad application prospects in the field of electrophysiological monitoring. Attached Figure Description

[0011] Figure 1 This is a flowchart illustrating the preparation process of a dual-network electrospinning reinforced hydrogel fiber film according to an embodiment of the present invention.

[0012] Figure 2 This is an optical microscope image of a sodium alginate-acrylamide dual-network hydrogel fiber film according to an embodiment of the present invention.

[0013] Figure 3 This is an optical microscope image of a polyvinyl alcohol-glycerol / gelatin dual-network hydrogel fiber film according to an embodiment of the present invention.

[0014] Figure 4 This is a physical image of a hydrogel fiber film according to an embodiment of the present invention.

[0015] Figure 5 This is a thickness test curve of the hydrogel fiber film according to an embodiment of the present invention.

[0016] Figure 6 This is a schematic diagram of the structure of an electrocardiogram sensor based on a gold fiber-hydrogel fiber film according to an embodiment of the present invention.

[0017] Figure 7 This is a test diagram of an electrocardiogram sensor based on a gold fiber film according to an embodiment of the present invention.

[0018] Figure 8 This is a test diagram of an electrocardiogram sensor based on a gold fiber-hydrogel fiber film according to an embodiment of the present invention.

[0019] Figure 9 This is a schematic diagram of the structure of a sweat sensor according to an embodiment of the present invention.

[0020] Figure 10 This is a test curve of sweat volume using a sweat sensor according to an embodiment of the present invention.

[0021] Figure 11 This is a schematic diagram of the structure of a flexible electrochemical sensor according to an embodiment of the present invention.

[0022] Figure 12 This is a pulse voltammetry curve of a flexible electrochemical sensor according to an embodiment of the present invention in copper ion solutions of different concentrations.

[0023] Figure 13 This is a graph showing the relationship between the peak current and copper ion concentration of a flexible electrochemical sensor according to an embodiment of the present invention.

[0024] Figure 14 The strain-stress curves of polyurethane fiber film, sodium alginate-acrylamide dual-network hydrogel fiber film, and polyvinyl alcohol-glycerol / gelatin dual-network hydrogel fiber film according to embodiments of the present invention are shown.

[0025] Figure labels: 1 is hydrogel precursor solution; 2 is electrospun fiber; 3 is hydrogel fiber film; 4 is gold fiber film; 5 is PEDOT / PSS electrode; 6 is silver / silver chloride fiber film. Detailed Implementation

[0026] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0027] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0028] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0029] To facilitate understanding of this invention, certain technical and scientific terms are specifically defined below. Unless explicitly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by one of ordinary skill in the art to which this invention pertains. In the description of this invention, the terms used herein have been explained and described; these explanations and descriptions are merely for the purpose of facilitating understanding and should not be construed as limiting the scope of protection of this invention.

[0030] In this paper, the term "interlocking structure" refers to a stable combination of two or more components through physical interlocking, mechanical interlocking, or spatial interpenetration. In this invention, it refers to the hydrogel filling the pores of the fiber membrane, with the hydrogel's network structure "anchored" in the pores of the fiber network, forming a mechanical interlock.

[0031] In this article, the term "electrospinned fiber film" refers to a porous film material prepared by electrospinning, which is formed by the interweaving and stacking of nano- to micro-scale fibers.

[0032] The technical solution of this application is described in detail below: hydrogel fiber film In some embodiments of the present invention, a hydrogel fiber film is proposed. According to an embodiment of the present invention, the hydrogel fiber film comprises: a fiber film base layer and a dual-network hydrogel, wherein the dual-network hydrogel comprises sodium alginate-acrylamide or polyvinyl alcohol-glycerol / gelatin, and the fiber film base layer comprises an electrospun fiber film; wherein the fiber film base layer has a porous structure, and the dual-network hydrogel is disposed within the porous structure of the fiber film base layer. The dual-network hydrogel in the hydrogel fiber film proposed by the present invention forms an interlocking structure with the fiber film base layer, exhibiting good mechanical and tensile properties, while also imparting adhesiveness not found in PU fiber films, thus possessing excellent adhesion ability and enhancing the mechanical properties of the PU fiber film. It can serve as an excellent ultrathin adhesive mass transfer layer and has broad application prospects in the field of electrophysiological monitoring.

[0033] According to an embodiment of the present invention, the thickness of the hydrogel fiber film is 1 μm to 30 μm. Exemplarily, the thickness of the hydrogel fiber film is 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, 26 μm, 28 μm or 30 μm, or a range between any two of the above values. According to a preferred embodiment of the present invention, the thickness of the hydrogel fiber film is 1 μm to 20 μm.

[0034] According to embodiments of the present invention, the fiber diameter in the fiber film substrate is 0.5 μm to 30 μm. Exemplarily, the fiber diameter in the fiber film substrate is 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, 26 μm, 28 μm, or 30 μm, or a range between any two of the above values. According to some preferred embodiments of the present invention, the fiber diameter in the fiber film substrate is 0.5 μm to 20 μm.

[0035] According to embodiments of the present invention, the electrospun fiber film is composed of at least one of the following polymers: polyurethane, thermoplastic polyurethane, styrene-butadiene-styrene block copolymer, hydrogenated styrene block copolymer, polydimethylsiloxane, and polyimide. A hydrogel network with an electrospun fiber network as a scaffold provides the fiber film with adhesiveness, hydrophilicity, and biocompatibility.

[0036] According to an embodiment of the present invention, the sodium alginate-acrylamide comprises water and the following components: acrylamide, sodium alginate, acrylamide crosslinking agent, sodium alginate crosslinking agent, acrylamide crosslinking thermal initiator, and acrylamide crosslinking catalyst.

[0037] According to embodiments of the present invention, the mass fraction of the acrylamide is 2% to 15%. Exemplarily, the mass fraction of the acrylamide is 2%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of the acrylamide is 4% to 12%.

[0038] According to embodiments of the present invention, the mass fraction of sodium alginate is 0.5% to 1.8%. Exemplarily, the mass fraction of sodium alginate is 0.5%, 0.52%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.56%, 1.6%, or 1.8%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of sodium alginate is 0.52% to 1.56%.

[0039] According to embodiments of the present invention, the mass fraction of the acrylamide crosslinking agent is 0.0025% to 0.0075%. Exemplarily, the mass fraction of the acrylamide crosslinking agent is 0.0025%, 0.003%, 0.0035%, 0.004%, 0.0045%, 0.005%, 0.0055%, 0.006%, 0.0065%, 0.007%, or 0.0075%, or a range between any two of the above values.

[0040] According to embodiments of the present invention, the mass fraction of the sodium alginate crosslinking agent is 0.05% to 0.25%. Exemplarily, the mass fraction of the sodium alginate crosslinking agent is 0.05%, 0.06%, 0.065%, 0.069%, 0.07%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.207%, 0.21%, 0.22%, 0.24%, or 0.25%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of the sodium alginate crosslinking agent is 0.069% to 0.207%.

[0041] According to embodiments of the present invention, the mass fraction of the acrylamide crosslinking thermal initiator is 0.02% to 0.2%. Exemplarily, the mass fraction of the acrylamide crosslinking thermal initiator is 0.02%, 0.03%, 0.035%, 0.039%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.11%, 0.117%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, or 0.2%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of the acrylamide crosslinking thermal initiator is 0.039% to 0.117%.

[0042] According to embodiments of the present invention, the mass fraction of the acrylamide crosslinking catalyst is 0.2% to 1.2%. Exemplarily, the mass fraction of the acrylamide crosslinking catalyst is 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.75%, 0.78%, 0.8%, 0.9%, 1%, 1.2%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of the acrylamide crosslinking catalyst is 0.26% to 0.78%.

[0043] According to embodiments of the present invention, the acrylamide crosslinking agent comprises at least one of the following: N,N'-methylenebisacrylamide, N,N'-diallyl tartrate diamide, divinylbenzene, or polyethylene glycol diacrylate.

[0044] According to an embodiment of the present invention, the sodium alginate crosslinking agent includes at least one of the following: calcium carbonate or calcium sulfate.

[0045] According to an embodiment of the present invention, the acrylamide crosslinking thermal initiator includes at least one of the following: potassium persulfate, sodium persulfate, or ammonium persulfate.

[0046] According to an embodiment of the present invention, the acrylamide crosslinking catalyst comprises at least one of the following: tetramethylethylenediamine, sodium sulfite, or sodium thiosulfate.

[0047] According to an embodiment of the present invention, the polyvinyl alcohol-glycerol / gelatin comprises water and the following components: polyvinyl alcohol, gelatin, glycerol and a crosslinking agent.

[0048] According to embodiments of the present invention, the mass fraction of the polyvinyl alcohol is 5% to 20%. Exemplarily, the mass fraction of the polyvinyl alcohol is 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, or 20%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of the polyvinyl alcohol is 8% to 20%.

[0049] According to an embodiment of the present invention, the mass fraction of the gelatin is 1% to 5%. For example, the mass fraction of the gelatin is 1%, 2%, 3%, 4% or 5%, or a range between any two of the above values.

[0050] According to embodiments of the present invention, the mass fraction of glycerol is 0.5% to 5%. Exemplarily, the mass fraction of glycerol is 0.5%, 1%, 2%, 3%, 4% or 5%, or a range between any two of the above values. According to some preferred embodiments of the present invention, the mass fraction of glycerol is 0.5% to 3%.

[0051] According to an embodiment of the present invention, the mass fraction of the crosslinking agent is 2% to 15%. For example, the mass fraction of the crosslinking agent is 2%, 4%, 5%, 6%, 8%, 10%, 12%, 14% or 15%, or a range between any two of the above values.

[0052] According to an embodiment of the present invention, the polyvinyl alcohol is selected from at least one of the following: PVA-1788, PVA-1799, and PVA-2480.

[0053] According to an embodiment of the present invention, the gelatin further comprises at least one of the following: chitosan, starch, or polyethylene oxide.

[0054] According to embodiments of the present invention, the crosslinking agent includes at least one of the following: boric acid, succinic acid, glutaraldehyde, acetaldehyde, or ammonium persulfate.

[0055] Preparation method In some embodiments of the present invention, a method for preparing the aforementioned hydrogel fiber film is provided. According to embodiments of the present invention, as shown in the appendix… Figure 1 As shown, the method includes: placing the fiber film substrate in a dual-network hydrogel precursor solution and performing gelation treatment to obtain a hydrogel fiber film. The hydrogel fiber film prepared by the method proposed in this invention possesses excellent mechanical and tensile properties, as well as good adhesion ability, making it a promising ultrathin adhesive mass transfer layer with broad application prospects in the field of electrophysiological monitoring.

[0056] According to an embodiment of the present invention, the method further includes: the fiber film substrate is prepared by an electrospinning process.

[0057] According to an embodiment of the present invention, the electrospinning uses a 26, 27 or 28 gauge needle.

[0058] According to embodiments of the present invention, the positive voltage of the spinner is 15 kV to 25 kV. Exemplarily, the positive voltage of the spinner is 15 kV, 16 kV, 17 kV, 18 kV, 19 kV, 20 kV, 21 kV, 22 kV, 23 kV, 24 kV or 25 kV, or a range between any two of the above values. According to some preferred embodiments of the present invention, the positive voltage of the spinner is 15 kV to 22 kV.

[0059] According to an embodiment of the present invention, the negative voltage of the spinner is -0.2 kV to 0 kV. Exemplarily, the negative voltage of the spinner is -0.2 kV, -0.15 kV, -0.1 kV or 0 kV, or a range between any two of the above values.

[0060] According to embodiments of the present invention, the injection speed is 0.01 mm / min to 0.05 mm / min. Exemplarily, the injection speed is 0.01 mm / min, 0.02 mm / min, 0.03 mm / min, 0.04 mm / min or 0.05 mm / min, or a range between any two of the above values. According to some preferred embodiments of the present invention, the injection speed is 0.02 mm / min to 0.04 mm / min.

[0061] According to an embodiment of the present invention, the receiving distance is 20 cm to 30 cm. Exemplarily, the receiving distance is 20 cm, 21 cm, 22 cm, 23 cm, 24 cm, 25 cm, 26 cm, 27 cm, 28 cm, 29 cm or 30 cm, or a range between any two of the above values. According to some preferred embodiments of the present invention, the receiving distance is 22 cm to 26 cm.

[0062] According to an embodiment of the present invention, the injection time is 5 min to 20 min. For example, the injection time is 5 min, 6 min, 8 min, 10 min, 12 min, 14 min, 15 min, 16 min, 18 min or 20 min, or a range between any two of the above values.

[0063] According to an embodiment of the present invention, the fiber film substrate further includes oxygen plasma treatment to obtain a surface-hydrophilic fiber film.

[0064] According to an embodiment of the present invention, the parameters of the oxygen plasma treatment are as follows: According to embodiments of the present invention, the oxygen plasma treatment power is 60W~100W. Exemplarily, the power is 60W, 65W, 70W, 75W, 80W, 85W or 90W, or a range between any two of the above values. According to some preferred embodiments of the present invention, the power is 70W~90W.

[0065] According to embodiments of the present invention, the oxygen flow rate is 90 sccm to 120 sccm. Exemplarily, the oxygen flow rate is 90 sccm, 95 sccm, 100 sccm, 110 sccm, 115 sccm, 120 sccm, or a range between any two of the above values. According to some preferred embodiments of the present invention, the oxygen flow rate is 95 sccm to 110 sccm.

[0066] Here, "sccm" refers to the volume of gas flowing through a cross-section per minute under standard temperature and pressure (STP) conditions, expressed in cubic centimeters per minute. Unless otherwise specified, sccm defaults to the volumetric flow rate at 0°C and 1 atm.

[0067] According to embodiments of the present invention, the oxygen plasma treatment time is 0.5 min to 2 min. Exemplarily, the treatment time is 0.5 min, 0.6 min, 0.8 min, 1 min, 1.2 min, 1.4 min, 1.5 min, 1.6 min, 1.8 min or 2 min, or a range between any two of the above values. According to some preferred embodiments of the present invention, the treatment time is 0.5 min to 1.4 min.

[0068] According to an embodiment of the present invention, the dual-network hydrogel precursor solution further includes a conductive agent, which enables the hydrogel to have good electrical conductivity while maintaining good mechanical properties and adhesion.

[0069] According to embodiments of the present invention, the conductive agent includes at least one of the following: silver nanowires, silver nanosheets, carbon nanotubes, or ionic liquids.

[0070] According to an embodiment of the present invention, the dual-network hydrogel precursor solution is a sodium alginate-acrylamide dual-network hydrogel, and the gelation treatment has at least one of the following technical features: According to embodiments of the present invention, the vacuum evacuation time is 2 min to 8 min. Exemplarily, the vacuum evacuation time is 2 min, 3 min, 4 min, 5 min, 6 min, 7 min or 8 min, or a range between any two of the above values. According to some preferred embodiments of the present invention, the vacuum evacuation time is 4 min to 6 min.

[0071] According to an embodiment of the present invention, the thin film after vacuum extraction is subjected to heat treatment.

[0072] According to embodiments of the present invention, the heating temperature is 50°C to 70°C. Exemplarily, the heating temperature is 50°C, 55°C, 60°C, 65°C or 70°C, or a range between any two of the above values. According to some preferred embodiments of the present invention, the heating temperature is 55°C to 65°C.

[0073] According to an embodiment of the present invention, the heating time is 2 h to 4 h. Exemplarily, the heating time is 2 h, 2.5 h, 3 h, 3.5 h or 4 h, or a range between any two of the above values. According to some preferred embodiments of the present invention, the heating time is 2.5 h to 3.5 h.

[0074] According to an embodiment of the present invention, the dual-network hydrogel precursor solution is a polyvinyl alcohol-glycerol / gelatin dual-network hydrogel, and the gelation treatment has at least one of the following technical features: According to embodiments of the present invention, the vacuum evacuation time is 2 min to 8 min. Exemplarily, the vacuum evacuation time is 2 min, 3 min, 4 min, 5 min, 6 min, 7 min or 8 min, or a range between any two of the above values. According to some preferred embodiments of the present invention, the vacuum evacuation time is 4 min to 6 min.

[0075] According to an embodiment of the present invention, the film after vacuum evacuation is subjected to freeze-thaw treatment.

[0076] According to an embodiment of the present invention, the freeze-thaw process includes: quick freezing with liquid nitrogen and standing at room temperature.

[0077] According to an embodiment of the present invention, the liquid nitrogen quick-freezing is performed for 1 min to 3 min. For example, the liquid nitrogen quick-freezing process is 1 min, 2 min or 3 min.

[0078] According to an embodiment of the present invention, the room temperature standing time is 10 min to 20 min. For example, the room temperature standing time is 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, or any range between two of the above values. According to some preferred embodiments of the present invention, the room temperature standing time is 14 min to 16 min.

[0079] According to an embodiment of the present invention, the freeze-thaw treatment is performed 3, 4 or 5 times, preferably 5 times.

[0080] Applications and wearable sensors In some embodiments of the present invention, the use of the aforementioned hydrogel fiber film in the fabrication of wearable sensors is proposed. The wearable sensor proposed by the present invention possesses excellent mechanical properties, adhesion, and biocompatibility, enabling it to achieve good adhesion to skin and other films.

[0081] According to the embodiments provided in this aspect, the wearable sensor includes at least one of the following: a fiber-based biosensor, a flexible electrophysiological signal sensor, a sweat sensor, or a flexible electrochemical sensor.

[0082] In some embodiments of the present invention, a wearable sensor is proposed. According to embodiments of the present invention, the wearable sensor comprises the aforementioned hydrogel fiber film. The wearable sensor proposed in this invention possesses excellent mechanical properties, adhesion, and biocompatibility, enabling it to achieve good adhesion to skin and other films.

[0083] Embodiments of the present invention will now be described in more detail, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the invention, and should not be construed as limiting the invention.

[0084] Example 1: Preparation of sodium alginate-acrylamide hydrogel fiber film Under heating conditions of 50°C, 0.156g of sodium alginate (purchased from Sigma) powder was completely dissolved in deionized water. Then, 1.25g of acrylamide (purchased from Sigma) was added to the solution. After complete dissolution, the solution temperature was lowered to 45°C. 0.00075g of N,N'-methylenebisacrylamide (purchased from Sigma), 0.0117g of ammonium persulfate (purchased from Sigma), 0.0207g of calcium carbonate (purchased from Xianfeng Nano, particle size 20nm), and 0.077g of tetramethylethylenediamine (purchased from Sigma) were added and, after complete dissolution, a certain mass of deionized water was added to prepare a solution with a total mass of 20g. After thorough stirring, the sodium alginate-acrylamide (SA-AAm) hydrogel precursor solution was obtained.

[0085] A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25g of polyurethane (PU) granules (purchased from Tecoflex, SG-85A) and 12.75g of solvent were weighed and poured into a 20ml brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60℃ water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15g to offset solvent evaporation during heating, forming a homogeneous system of PU granules dissolved in the solvent. The resulting homogeneous system was injected into a 5ml syringe using a 27-gauge needle. The spinner was set to a positive voltage of 18V and a negative voltage of -0.2V; the injection speed was 0.03mm / min; the receiving distance was 25cm; and the injection time was 15min. Aluminum foil could be used as the receiving substrate. The fiber film was peeled off the tin foil in deionized water at 50℃ and dried thoroughly. Then, a hydrophilic fiber film was obtained by oxygen plasma treatment. The process parameters for oxygen plasma treatment were as follows: power of 80W, oxygen flow rate of 100 sccm, and time of 1min.

[0086] The plasma-treated polymer fiber film was immediately placed in the SA-AAm hydrogel precursor solution, vacuumed for 5 minutes, placed in a stainless steel reactor, and then heated in an oven at 60°C for 3 hours. After gelation, the film was removed and the surface of the film was washed with deionized water to obtain the sodium alginate-acrylamide (SA-AAm) double-network hydrogel fiber film.

[0087] Introducing electrospinning technology into a hydrogel fiber film within a dual-network hydrogel improves its mechanical properties. Compared to traditional dual-network hydrogels, this electrospun fiber network-reinforced hydrogel exhibits superior porosity (see...). Figure 2 ) and tensile properties (see Figure 4 The film thickness was measured to be approximately 8 μm using a film thickness gauge. Figure 5The dual-network electrospun reinforced hydrogel, due to its excellent adhesion and ultra-thin properties, provides consistent contact with the skin.

[0088] Example 2: Preparation of polyvinyl alcohol-glycerol / gelatin hydrogel fiber film Under heating conditions of 90℃, 2.25 g of polyvinyl alcohol (PVA) powder (model 1788, purchased from Sinopharm) was completely dissolved in deionized water. Then, 0.2025 g of gelatin (purchased from Sinopharm) and 0.1215 g of glycerol (purchased from Sinopharm) were added sequentially. After complete dissolution, a certain mass of deionized water was added to prepare a hydrogel precursor solution with a total mass of 15 g, thus obtaining a polyvinyl alcohol-glycerol / gelatin (PVA-Gly / Gel) hydrogel precursor solution.

[0089] A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25 g of polyurethane (PU) granules (purchased from Tecoflex, SG-85A) and 12.75 g of solvent were weighed and poured into a 20 mL brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60°C water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15 g to offset solvent evaporation during heating, forming a homogeneous system of PU granules dissolved in the solvent. The resulting homogeneous system was injected into a 5 mL syringe using a 27-gauge needle. The spinneret was set to a positive voltage of 18 V and a negative voltage of -0.2 V; the injection speed was 0.03 mm / min; the receiving distance was 25 cm; and the injection time was 8 min. Aluminum foil could be used as the receiving substrate. The fiber film was peeled off the tin foil in deionized water at 50℃ and dried thoroughly. Then, a hydrophilic fiber film was obtained by oxygen plasma treatment. The process parameters for oxygen plasma treatment were as follows: power of 80W, oxygen flow rate of 100 sccm, and time of 1min.

[0090] The plasma-treated polymer fiber film was immediately immersed in a PVA-Gly / Gel hydrogel precursor solution. After vacuum evacuation for 5 minutes, the film was removed and placed in liquid nitrogen for 2 minutes. This process was repeated 5 times, with the film then placed in a 5% w / w boric acid solution (purchased from Sinopharm) for 10 minutes. The film surface was then washed with deionized water to obtain a polyvinyl alcohol-glycerol / gelatin (PVA-Gly / Gel) dual-network hydrogel fiber film. This hydrogel fiber film exhibits a porous fiber morphology (see...). Figure 3 ).

[0091] Example 3 Wearable ECG Sensor A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25g of PU particles (purchased from Tecoflex, SG-85A) and 12.75g of solvent were weighed and poured into a 20ml brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60℃ water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15g to offset solvent evaporation during heating, forming a homogeneous system of PU particles dissolved in the solvent. The resulting homogeneous system was injected into a 5ml syringe using a 26-gauge needle. The spinneret was set to a positive voltage of 18V and a negative voltage of -0.2V; the injection speed was 0.06mm / min; the receiving distance was 20cm; and the injection time was 30min. Aluminum foil could be used as the receiving substrate. After peeling the fiber membrane off the tin foil, a gold layer with a thickness of 200 nm is sputtered onto the fiber film using magnetron sputtering technology to obtain a gold fiber film, which serves as the electrode layer of the electrocardiogram sensor.

[0092] A single-lead ECG electrode was fabricated by placing a gold fiber film on the surface of an SA-AAm dual-network hydrogel fiber film (as shown in Example 1), with the structure as follows. Figure 6 As shown. The aforementioned ECG electrodes were placed on the test subject's arm to form a single-lead ECG monitoring circuit, and the ECG signal was measured via a portable wearable circuit with Bluetooth.

[0093] Compared to ECG electrodes made only of gold fiber films ( Figure 7 As shown), an ECG electrode with a hydrogel fiber film as the adhesion layer between the gold fiber electrode and the skin can obtain a good ECG signal waveform, such as... Figure 8 As shown in the figure. This result is due to the softness and high adhesion of the aforementioned hydrogel.

[0094] Example 4: Sweat Sensor A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25g of PU particles (purchased from Tecoflex, SG-85A) and 12.75g of solvent were weighed and poured into a 20ml brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60℃ water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15g to offset solvent evaporation during heating, forming a homogeneous system of PU particles dissolved in the solvent. The resulting homogeneous system was injected into a 5ml syringe using a 26-gauge needle. The spinneret was set to a positive voltage of 18V and a negative voltage of -0.2V; the injection speed was 0.06mm / min; the receiving distance was 20cm; and the injection time was 30min. Aluminum foil could be used as the receiving substrate.

[0095] After peeling the PU fiber film off the aluminum foil, a poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS, purchased from Sigma) pattern is sprayed onto the fiber film as the functional material layer and electrode layer of the sweat volume sensor. The PU fiber film with PEDOT:PSS electrodes and the hydrogel fiber film (as shown in Example 2) are then bonded together to obtain a sweat sensor, the structure of which is as follows. Figure 9 As shown. The experimental results are as follows. Figure 10 As shown, the resistance of the test sensor gradually increases with the increase of sweating time, indicating that the sensor can be used for monitoring human sweating.

[0096] Example 5 Flexible Electrochemical Sensor A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25g of PU particles (purchased from Tecoflex, SG-85A) and 12.75g of solvent were weighed and poured into a 20mL brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60℃ water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15g to offset solvent evaporation during heating, forming a homogeneous system of PU particles dissolved in the solvent. The resulting homogeneous system was injected into a 5mL syringe using a 26-gauge needle. The spinneret was set to a positive voltage of 18V and a negative voltage of -0.2V; the injection speed was 0.06mm / min; the receiving distance was 20cm; and the injection time was 30min. Aluminum foil could be used as the receiving substrate. Electrospinning + Dual-Network Hydrogel After peeling the fiber film off the tin foil, a gold layer with a thickness of 200 nm is sputtered onto the fiber film using magnetron sputtering technology to obtain the gold fiber film working electrode.

[0097] A silver / silver chloride fiber film reference electrode was prepared by screen printing a silver / silver chloride paste (purchased from Sigma) onto another fiber film and drying it at 70°C for 3 hours. The silver / silver chloride reference electrode, the hydrogel fiber film (as shown in Example 2), and the gold working electrode were then assembled in sequence to obtain the fiber-based electrochemical sensor, the structure of which is shown below. Figure 11 As shown. Using pulse voltammetry, this sensor can be used to detect copper ion solutions with concentrations ranging from 100 to 1000 μg / L, such as... Figure 12 and Figure 13 As shown in the figure. This result indicates that the sensor holds promise for use as a flexible electrochemical sensor for detecting biochemical ions such as copper, magnesium, and calcium ions.

[0098] Example 6 Performance determination of hydrogel fiber films A solvent was prepared by mixing tetrahydrofuran (purchased from Aladdin) and dimethylformamide (purchased from Aladdin) at a mass ratio of 1:1. 2.25g of PU particles (purchased from Tecoflex, SG-85A) and 12.75g of solvent were weighed and poured into a 20ml brown reagent bottle. The reagent bottle was placed in a stainless steel reactor and heated in a 60℃ water bath with stirring for 3 hours. After heating, the solvent was added to a final volume of 15g to offset solvent evaporation during heating, forming a homogeneous system of PU particles dissolved in the solvent. The resulting homogeneous system was injected into a 5mL syringe using a 27-gauge needle. The spinneret was set to a positive voltage of 18V and a negative voltage of -0.2V; the injection speed was 0.03 mm / min; the receiving distance was 25cm; and the injection time was 8min. Aluminum foil could be used as the receiving substrate. Using a 300μm thick polyimide film as a framework in deionized water at 50℃, the fiber film is peeled off from the tin foil and dried thoroughly to obtain the PU fiber film.

[0099] SA-AAm dual-network hydrogel fiber films and PVA-Gly / Gel dual-network hydrogel fiber films were prepared respectively.

[0100] The surface of the PU fiber film was treated with oxygen plasma technology. The oxygen plasma power was 80W, the oxygen flow rate was 100 sccm, and the treatment time was 1 min. The polymer fiber film was immediately placed in the SA-AAm hydrogel precursor solution, vacuumed for 5 min, placed in a stainless steel reactor, and then heated in an oven at 60°C for 3 hours. After gelation, the film was removed, and the surface was washed with deionized water to obtain the SA-AAm double-network hydrogel fiber film.

[0101] The surface of the PU fiber film was treated with oxygen plasma technology. The oxygen plasma power was 80W, the oxygen flow rate was 100 sccm, and the treatment time was 1 min. The polymer fiber film was immediately placed in a PVA-Gly / Gel hydrogel precursor solution and vacuumed for 5 min. The film was then removed and placed in liquid nitrogen for 2 min. The film was then removed again and placed at room temperature for 15 min. This freeze-thaw cycle was repeated 5 times. Afterward, the film was placed in a 5% w / w boric acid solution (purchased from Sinopharm) for 10 min. The film surface was then washed with deionized water to obtain the PVA-Gly / Gel double-network hydrogel fiber film.

[0102] The mechanical properties of the hydrogel fiber film were tested using a strain testing system, and the results are as follows: Figure 14As shown. Under the same strain conditions, compared with PU fiber film, both SA-AAm dual-network hydrogel fiber film and PVA-Gly / Gel dual-network hydrogel fiber film can withstand greater stress and have better mechanical properties. Furthermore, the tensile properties of SA-AAm dual-network hydrogel fiber film are better than those of PVA-Gly / Gel. Combined with morphology analysis results (see...), Figure 2 , Figure 3 ) and adhesion properties results (see Figure 4 The dual-network electrospinning reinforced hydrogel fiber film technology not only maintains the original porous structure of PU fiber film, but also imparts adhesion that PU fiber film does not have, and enhances the mechanical properties of PU fiber film.

[0103] In this invention, unless otherwise explicitly specified and limited, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" of the second feature can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.

[0104] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0105] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A hydrogel fiber film, characterized in that, include: A fiber film base layer and a dual-network hydrogel, wherein the dual-network hydrogel comprises sodium alginate-acrylamide or polyvinyl alcohol-glycerol / gelatin, and the fiber film base layer comprises an electrospun fiber film; The fiber film substrate has a porous structure, and the dual-network hydrogel is disposed in the porous structure of the fiber film substrate.

2. The hydrogel fiber film according to claim 1, characterized in that, The thickness of the hydrogel fiber film is 1 μm to 30 μm; Optionally, the fiber diameter in the fiber film substrate is 0.5 μm to 30 μm; Optionally, the electrospun fiber film is composed of at least one of the following polymers: polyurethane, thermoplastic polyurethane, styrene-butadiene-styrene block copolymer, hydrogenated styrene block copolymer, polydimethylsiloxane, and polyimide.

3. The hydrogel fiber film according to claim 1, characterized in that, The sodium alginate-acrylamide comprises water and the following components: acrylamide, sodium alginate, acrylamide crosslinking agent, sodium alginate crosslinking agent, acrylamide crosslinking thermal initiator, and acrylamide crosslinking catalyst; Optionally, the acrylamide has a mass fraction of 2% to 15%; Optionally, the sodium alginate has a mass fraction of 0.5% to 1.8%. Optionally, the mass fraction of the acrylamide crosslinking agent is 0.0025% to 0.0075%; Optionally, the mass fraction of the sodium alginate crosslinking agent is 0.05% to 0.25%; Optionally, the mass fraction of the acrylamide crosslinking thermal initiator is 0.02% to 0.2%; Optionally, the mass fraction of the acrylamide crosslinking catalyst is 0.2% to 1.2%; Optionally, the acrylamide crosslinking agent comprises at least one of the following: N,N'-methylenebisacrylamide, N,N'-diallyl tartrate diamide, divinylbenzene, or polyethylene glycol diacrylate; Optionally, the sodium alginate crosslinking agent includes at least one of the following: calcium carbonate or calcium sulfate; Optionally, the acrylamide crosslinking thermal initiator includes at least one of the following: potassium persulfate, sodium persulfate, or ammonium persulfate; Optionally, the acrylamide crosslinking catalyst comprises at least one of the following: tetramethylethylenediamine, sodium sulfite, or sodium thiosulfate.

4. The hydrogel fiber film according to claim 1, characterized in that, The polyvinyl alcohol-glycerol / gelatin comprises water and the following components: polyvinyl alcohol, gelatin, glycerol, and a crosslinking agent; Optionally, the polyvinyl alcohol has a mass fraction of 5% to 20%; Optionally, the gelatin has a mass fraction of 1% to 5%; Optionally, the glycerol has a mass fraction of 0.5% to 5%; Optionally, the crosslinking agent has a mass fraction of 2% to 15%; Optionally, the polyvinyl alcohol is selected from at least one of the following: PVA-1788, PVA-1799, PVA-2480; Optionally, the gelatin further comprises at least one of the following: chitosan, starch, or polyethylene oxide; Optionally, the crosslinking agent includes at least one of the following: boric acid, succinic acid, glutaraldehyde, acetaldehyde, or ammonium persulfate.

5. A method for preparing the hydrogel fiber film according to any one of claims 1 to 4, characterized in that, include: The fiber film substrate is placed in a double-network hydrogel precursor solution and gelled to obtain a hydrogel fiber film.

6. The method according to claim 5, characterized in that, The method further includes: the fiber film substrate is prepared by an electrospinning process; Optionally, the electrospinning uses a 26-28 gauge needle; Optionally, the positive voltage of the spinner is 15 kV to 25 kV; Optionally, the negative voltage of the spinner is -0.2 kV to 0 kV; Optionally, the injection rate is 0.01 mm / min to 0.05 mm / min; Optionally, the receiving distance is 20 cm to 30 cm; Optionally, the injection time is 5 min to 20 min; Optionally, the fiber film substrate further includes oxygen plasma treatment; Optionally, the dual-network hydrogel precursor solution further includes a conductive agent; Optionally, the conductive agent includes at least one of the following: silver nanowires, silver nanosheets, carbon nanotubes, or ionic liquids.

7. The method according to claim 5, characterized in that, The dual-network hydrogel precursor solution is sodium alginate-acrylamide dual-network hydrogel, and the gelation treatment includes: vacuum degassing for 2 min to 8 min. Optionally, the vacuum-evacuated film is subjected to heat treatment; Optionally, the heating temperature is 50℃~70℃; Optionally, the heating time is 2 h to 4 h.

8. The method according to claim 5, characterized in that, The dual-network hydrogel precursor solution is a polyvinyl alcohol-glycerol / gelatin dual-network hydrogel, and the gelation treatment includes: vacuum degassing for 2 min to 8 min. Optionally, the vacuum-evacuated film is subjected to freeze-thaw treatment; Optionally, the freeze-thaw process includes: quick freezing with liquid nitrogen and standing at room temperature; Optionally, the liquid nitrogen quick-freezing is performed for 1 min to 3 min; Optionally, the standing at room temperature is carried out for 10 min to 20 min; Optionally, the freeze-thaw treatment is performed 3 to 5 times.

9. Use of the hydrogel fiber film according to any one of claims 1 to 4 in the preparation of wearable sensors.

10. The use according to claim 9, characterized in that, The wearable sensor includes at least one of the following: a fiber-based biosensor, a flexible electrophysiological signal sensor, a sweat sensor, or a flexible electrochemical sensor.

11. A wearable sensor, characterized in that, include: The hydrogel fiber film according to any one of claims 1 to 4.